2022
DOI: 10.3389/fnins.2022.816752
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil Reduces Neuronal Pyroptosis and Cognitive Decline After Sleep Deprivation

Abstract: Sleep deprivation (SD) induces systemic inflammation that promotes neuronal pyroptosis. The purpose of this study was to investigate the effect of an antioxidant modafinil on neuronal pyroptosis and cognitive decline following SD. Using a mouse model of SD, we found that modafinil improved learning and memory, reduced proinflammatory factor (IL-1β, TNF-α, and IL-6) production, and increased the expression of anti-inflammatory factors (IL-10). Modafinil treatment attenuated inflammasome activity and reduced neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, NLRP3 inflammasome was expressed in a variety of cells, including astrocytes [ 38 ], endothelial cells [ 39 ], neutrophils and monocytes [ 20 ]. Moreover, our previous study has confirmed the promotion of neuronal pyroptosis under conditions of sleep deprivation [ 40 ]. Similarly, the assembly and activation of the NLRP3 inflammasome in dopamine neurons is also an important strategy to prevent the degeneration of neurons.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, NLRP3 inflammasome was expressed in a variety of cells, including astrocytes [ 38 ], endothelial cells [ 39 ], neutrophils and monocytes [ 20 ]. Moreover, our previous study has confirmed the promotion of neuronal pyroptosis under conditions of sleep deprivation [ 40 ]. Similarly, the assembly and activation of the NLRP3 inflammasome in dopamine neurons is also an important strategy to prevent the degeneration of neurons.…”
Section: Discussionmentioning
confidence: 74%
“…So far, it seems impossible to distinguish whether inflammatory cytokines in brain tissue are produced by microglia, neurons or other nerve cells. Levels of neuronal inflammatory cytokines have been studied in traumatic brain injury and sleep deprivation [ 40 , 63 ]. We cannot deny that miR-146a-5p affected the secretion of inflammatory cytokines in microglia cells.…”
Section: Discussionmentioning
confidence: 99%
“…Modafinil is a widely-used stimulant that was originally developed to treat paroxysmal narcolepsy. According to different research studies, modafinil improves NLRs inflammasome-mediated pyroptosis in mice with SD through increasing BDNF (brain-derived neurotrophic factor) stimulation in the hippocampus and synaptic plasticity, which in turn, improve learning, memory, and cognitive functions (Xiong et al, 2022). Signaling pathways of Nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome.…”
Section: Sd-induced Cognitive Decline: Targeting Nlrp3 Inflammasomementioning
confidence: 99%
“…Targeting the regulation of impaired neuronal pyroptosis and neuroinflammation may be a promising therapeutic strategy for treatment of SD. (Xiong et al, 2022) 9…”
Section: # Findings Referencesmentioning
confidence: 99%
“…The pathogenesis of SD associated with cognitive disorders is not very clear at present, in modern medicine, awakening promoters, and receptor inhibitors are the main drugs to promote sleep and improve cognition. [ 8 , 9 ] Although these drugs can extend the patients’ sleep time and improve cognition, they cannot solve the underlying problem of sleep deficiency and have great side effects in the long term. As the treasure of China, traditional Chinese acupuncture has a long history, safety, and effectiveness, and has been widely respected in clinical application.…”
Section: Introductionmentioning
confidence: 99%